HISTORY OF THE EMERGENCE OF LINGUISTIC THE TERM «INTERFERENCE» - Karimova Adolat Ibrogimovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Annotation: The article provides an interpretation of the term “interference” in various fields of science, outlines the history of the emergence of this phenomenon in linguistics with the participation of the American linguist Uriel Weinreich, and describes three types of interference that arise when teaching Russian to students at non-linguistic universities.